Analisis Dan Desain Sistem Informasi Penjualan Berbasis Web Menggunakan Metode Prototype - Muhammad Ikhsan Hafidz; Heru Sutejo; Inggrid Sheila Putri; Vigo Pahabol; Dimi Kogoya; Leth Kobak; Fredy R Molama (Tamilis Synex: Multidimensional Collaboration, 2026)
The rapid advancement of information technology has encouraged businesses to adopt digital solutions to improve operational efficiency and service quality. In the culinary sector, many small-scale food businesses still rely on manual sales processes, resulting in transaction recording errors, inefficient data management, and delays in customer service. This study aims to design a web-based yellow rice (nasi kuning) sales information system using the Prototype development method. The research method consists of five stages: requirements identification, prototype development, prototype evaluation, prototype refinement, and final system implementation. Data were collected through observation and interviews to identify user requirements and existing business process challenges. The proposed system is designed to provide essential functionalities, including administrator authentication, menu management, online ordering, transaction processing, customer management, and sales reporting. Unified Modeling Language (UML) diagrams, including use case, activity, and class diagrams, were utilized to model system requirements and workflows. The results of this study produce a comprehensive web-based sales system design that facilitates online food ordering, improves transaction management, and supports more structured sales data processing. The system is expected to enhance operational effectiveness, improve service quality, and provide greater convenience for both business owners and customers in managing and conducting sales transactions